Характеристика ліпідного спектра крові у хворих із пубертатними матковими кровотечами - Щербина, М. О.; Диннік, О. О.; Сулима, Т. Н. (Clinical Endocrinology and Endocrine Surgery, 2012)
Lipid metabolism features were investigated in 163 patients aged 11-18 years with pubertal uterine bleeding. Dyslipidemia was identified in 22.8% of patients, combined disorders in lipid profile were observed in 10.6% of the cases. Three main types of dyslipoproteinemia were revealed in the examined namely: 22-a and, 2V as well as and hypoalphaholesterinemia, the severity of which was the highest in patients’ with are overweight.